The Effect of Oxidation on The Structure and Hardness of (Zr, Hf)N Coatings - Atar, Erdem; Kayali, E.S.; Çimenoğlu, H. (Trans Tech Publications, Ltd., 2010)
In the present study, the effect of oxidation on the structure and the hardness of ternary (Zr, Hf)N coatings, whose Hf content was varied between 0 and 21 wt.%, has been systematically examined. Coatings were applied on AISI D2 tool steel plates by arc physical vapor deposition (PVD). Oxidation was conducted at 400oC for times up to 12 h in air. Ternary (Zr, Hf)N coatings are found to be more susceptible towards oxidation compared to binary ZrN coating. Oxidation caused the formation of a mixed oxide layer composed of ZrO2 and HfO2. Formation of oxide layer was accompanied by a reduction in hardness. Hardness values of Hf free and Hf alloyed (Zr, Hf)N coatings were very close to each other both in as-deposited and oxidized states.